Pengembangan media pembelajaran menggunakan model ADDIE - Maulidya, Baiq fina Fadhila (Maliki Interdisciplinary Journal, 2025)
the development of technology-based instructional media to improve learning effectiveness at Madrasah Ibtidaiyah (MI) and elementary school (SD) levels. The media development process considers principles of integration, affordability, usability, attractiveness, effectiveness, and alignment with learning objectives. Development follows a systematic process through needs analysis, design, development, implementation, evaluation, and revision, utilizing the ADDIE model. A case study highlights the development of Android-based mathematics instructional media using Unity 3D at SD Negeri 4 Padangkerta, focusing on cube and rectangular prism topics. Validation results indicate that the developed media achieved a feasibility score of 83.59%, categorized as "highly feasible." Additionally, the use of concrete media, such as physical three-dimensional models, is proposed to complement digital media and enhance students’ direct understanding of spatial concepts. The combination of digital and concrete media results in more effective, interactive, and engaging learning outcomes.